Marcus-Hush-Chidsey theory of electron transfer applied to voltammetry: A review - Henstridge, M; Laborda, E; Rees, N; Compton, R (2012)
The application of the Marcus-Hush-Chidsey (MHC) formalism to heterogeneous electron transfer processes is reviewed and compared with the commonly employed Butler-Volmer (BV) approach. The MHC model is potentially more powerful than BV since it enables us to analyze the electrode kinetics in terms of the microscopic nature of the electroactive species, electrode and solvent. Despite having been studied fairly extensively in the case of surface-bound redox couples, its application to heterogeneous electron transfer reactions has been limited. Here, we review the use of the MHC approach for the analysis of both surface-bound and solution phase redox systems and its suitability as a model for the parameterisation of electrode kinetics. Results obtained for several slow electrode reactions using cyclic voltammetry and reverse scan square wave voltammetry are reviewed which reveal that the simple MHC model does not always give a satisfactory fit to experimental data in contrast to BV parameterisation. Possible physical reasons for the experimental deviations from simple MHC theory are examined. © 2011 Elsevier Ltd.